Learning Motivation of Students with a Background Behind Broken Home at SMA Negeri 1 Geringging River - Alvazio, Alvazio; Wirasolina, Wirasolina; Joniadison, Joniadison (Lembaga Riset Mutiara Akbar, 2022)
This study aims to determine (1) the learning motivation of students is seen from the intrinsic factors with a broken home background (2) The students' learning motivation is seen from the extrinsic factors with a broken home background. This type of research is qualitative research. The data collection method used is interviews. The subjects of this study were JS and DV. while the additional informants are MS, FS, and SD. This data collection technique uses triangulation including method triangulation, inter-researcher triangulation, data source triangulation and theoretical triangulation. Meanwhile, to obtain valid data, this research was conducted by data triangulation. Triangulation is a technique of checking the validity of data by utilizing something outside the data. The results showed that. The results of the study show that: first, students do not get good encouragement from parents, do not provide encouragement and complement the needs of children so that children are enthusiastic and motivated to learn. Second, students have not been able to determine the ideals that exist within themselves. Third, the motivation of students in learning so far, students do not get support and support from parents. Fourth, students do not really care about teaching and learning activities. Fifth, children's learning environment is not conducive, this is because parents are indifferent and never provide facilities to children